Physical activity, sleep quality, energy dense nutrient-poor (EDNP) foods intake, with blood pressure among obese teachers - Nina Resti; Ani Margawati; Choirun Nissa; Diana Nur Afifah; Ahmad Syauqy; Charysa Zaimatussoleha (AcTion: Aceh Nutrition Journal, 2024)
Profession teachers with obesity nutritional status encourage hypertension because they have light physical activity, poor sleep quality, and high energy-dense, nutrient-poor food (EDNP) intake caused by potential occupational risks. This study sought to examine the relationship between physical activity, sleep quality, EDNP intake, and systolic and diastolic blood pressure. This was a study with a consecutive sampling design among female teachers aged 35-54 years in Kudus in March 2022. The total number of respondents with direct offline interviews was 59. Rank Spearman or Pearson test for bivariate analysis, followed by the linear regression test for multivariate analysis. Bivariate tests showed that physical activity (p=0,039) and EDNP intake (p=0,001) showed a noteworthy correlated with systolic blood pressure. The relationship between sleep quality (p=0,039) and EDNP intake (p=0,028) was significant for diastolic blood pressure but not for systolic blood pressure. The results of the multivariate test indicated a substantial correlation between physical activity, sleep quality, and EDNP intake on systolic BP (p=0,001) and diastolic BP (p=0,006) blood pressure. In conclusion, physical activity, sleep quality, and EDNP intake were significantly associated with systolic and diastolic blood pressure.